A LITERATURE REVIEW ON THE IMPACT OF AI TOOLS ON THE ORAL LANGUAGE SKILLS OF FOREIGN LANGUAGE LEARNERS - ERKINOV ERKIN TULKIN UGLI,; IMOMOVA JASMINA SHERALI QIZI, (TADQIQOTLAR, 2026)
Abstract. This literature review was to analyze empirical studies examining the impact of artificial intelligence (AI) tools on English as a Foreign Language (EFL) learners'  oral  communication  skills,  anxiety  levels,  and  motivation.  The  review encompasses four main studies: (1) a study investigating the multifaceted impact of AI on  speaking  skills,  anxiety,  and  motivation  through  a  pre-post  intervention  design involving 147 Chinese EFL learners; (2) a study examining the role of AI tools in developing verbal communication skills among six healthcare undergraduate students using the CLIP (Coherence, Lexical, Grammatical, Pronunciation) assessment criteria; (3) a mixed-methods quasi-experimental study measuring the effect of the Microsoft Teams Reading Progress (MTRP) AI tool on oral reading fluency (ORF) among 56 third-grade students in Saudi Arabia; (4) a study reviewing the overall effectiveness of AI-based pronunciation and speaking skills development tools. All studies indicate that AI has a positive impact on developing oral language skills, but should not completely replace traditional teaching methods.